The Effect of Firing Background on Some Soil Physico-Chemical Properties in Forest Ecosystem of Sardasht - S. Ashrafi-Saeidlou; MH. Rasouli-Sadghiani; M. Barin (علوم آب و خاک, 2017)
The Firing effect on soil depends on its intensity and duration. In order to investigate influence of different firing backgrounds on some soil physical and chemical properties, 80 soil samples were taken from two depths (0-5 cm and 5-20 cm) with different time of firing background (2 and 12 months). Some soil physical and chemical characteristics were measured at soil samples. The results showed that there was a significant difference in the amount of pH, EC, bulk density and ammonium in soils with different history of burning. The amount of studied indices increased after firing in burned soils compared to the control ones. However 12 months later they reach to their pre-fire levels. Total nitrogen amount in soils with 2 and 12 months firing history were 1.18 and 1.11 times higher than the control soils, respectively. The amount of organic carbon in surface depth (0-5 cm) of burned soils with 2 and 12 month firing backgrounds 37.25 and 24.7 percent increased in comparison to control soils, respectively. Also, fire led to a significant reduction in the amount of clay (29.25 percent) in burned areas compared to the control ones. Soil particle size distribution in control sites were in clay up to loam and in burned areas were in clay loam up to sandy loam classes. Therefore forest firing causes obvious changes in soil properties, remediation of which takes more than one year.